PENGARUH WAKTU PERENDAMAN BAJA DENGAN EKSTRAK BUAH PINANG DAN HCl TERHADAP LAJU KOROSI DAN POTENSIAL LOGAM - Mega Wahyuni (PILLAR OF PHYSICS, 2013)
Corrosion can not be prevented but rates can be reduced. One of the most effective ways to reduce the rate of corrosion is the use of organic inhibitors. The purpose of this study was to of this study was to obtain a corrosion inhibitor inexpensive and non-toxic. This research is experimental research with a sample of ASSAB 760 leading edge of materials that are medium carbon steel. immersioning steel with inhibitor in two ways, namely steel immersion areca extracts for 24 hours, then immersion with HCl (with inhibitor method I). Steel immersion with HCl + areca nut extract (with inhibitor method II). The independent variable is the variation of immersion time. The dependent variable such as the rate of corrosion inhibitor efficiency, potential. Control variables such as the type of steel used, the concentration of HCl, inhibitor concentration and temperature. By using this method of weight loss obtained corrosion rate and inhibitor efficiency. Potential metal obtained by direct measurement. From the results obtained with inhibitors steel immersion in acidic environments means I have a higher efficiency than soaking the inhibitor method II. From the overall results of the study showed that areca nut extract is an effective corrosion inhibitor for steel in acidic environment, because it can inhibit the corrosion rate with an efficiency of 61.31% - 74.56% by immersioning 12 hours, 24 hours and 36 hours. Keywords: medium carbon steel, areca nut extract, organic Inhibitor, weight loss method, immersion time.